Analysis of atomistic structural deformation characteristics of calcium silicate hydrate in 53-year-old tricalcium silicate paste using atomic pair distribution function. (20th March 2020) - Bae, Sungchul; Jee, Hyeonseok; Suh, Heongwon; Kanematsu, Manabu; Shiro, Ayumi; Machida, Akihiko; Watanuki, Tetsu; Shobu, Takahisa; Morooka, Satoshi; Geng, Guoqing; Suzuki, Hiroshi
Graphical abstract: Highlights: Pair distribution function analysis was performed on 53-year-old fully hydrated C3 S. 53-year-old C3 S paste was composed of C-S-H and Ca(OH)2 without carbonation. Macrostrain, strain in reciprocal space, and strain in real space were compared. 53-year-old C3 S paste possessed a higher E-modulus (18.3 GPa) than the 131-day-old C3 S paste (8.3 GPa) within 20 Å. Abstract: Although the atomistic structure and the deformation characteristics of calcium silicate hydrates (C-S-H) are of primary interest in cement chemistry, they have not been fully investigated. In this study, pair distribution function (PDF) analysis was conducted on a 53-year-old fully hydrated tricalcium silicate (C3 S) paste using in situ synchrotron high-energy X-ray scattering to probe the atomic structural deformation of C-S-H under external loading. The results were compared with those from our previous PDF study of a 131-day-old C3 S paste in order to elucidate the effect of aging on the mechanical characteristics of C-S-H. Three different strains measured by the strain gauge, by the lattice shifts (d-spacing) in the reciprocal space, and by the shift of the interatomic distance (r) in the real space were compared. In the range of r < 20 Å, where most of the information was derived from C-S-H, the 53-year-old C3 S paste had a higher overall elastic modulus (18.3 GPa) and better resistance to compressive stress than the 131-day-old C3 S paste (elastic modulus: 8.3 GPa). Moreover, it was found that the macroscopic strains of the 53-year-old C3 S paste were presumably induced by mechanical deformation such as microcracks at the macroscale. The results provide experimental evidence for the atomistic and mesoscale mechanical behavior of C-S-H in the early and late ages.